Pengaruh Model Pembelajaran Problem Based Learning (PBL) dengan Ceramah dan Konsep Diri (KD) Terhadap Nilai Aljabar Linear Mahasiswa - Ratna Puspita Indah; Anisatul Farida (Absis: Mathematics Education Journal, 2022)
One indicator of the success of a lesson is the achievement of high scores according to problem-solving abilities. This study aims to determine the interaction between the learning model and the level of student self-concept to determine a more effective learning model. This study uses a quantitative approach and analyzes the results with hypothesis testing. From the results of the test analysis, obtained the F value of 132.567 and Sig. 0.000, so there is a difference in Linear Algebra Values in the PBL Model and the Lecture Model. For the KD variable, the F value is 3.779 and the sig. 0.060, meaning that there is also a difference in Linear Algebra scores for students with high KD and low KD.